Tissue Distribution of Hirsutine and Hirsuteine in Mice by Ultrahigh-Performance Liquid Chromatography-Mass Spectrometry - Zhou, Quan (J Anal Methods Chem, 2020)
Hirsutine and hirsuteine were two alkaloid monomers extracted from the traditional Chinese medicine Uncaria rhynchophylla, which have pharmacological effects such as antihypertension, anti-infection, and heart protection. An ultrahigh-performance liquid chromatography-mass spectrometry was established for the determination of hirsutine and hirsuteine in tissues (liver, kidney, heart, spleen, brain, and lung), and their absorption, distribution, and metabolism were studied for providing information on its pharmacological mechanism. UPLC BEH C18 column (2.1  mm × 100  mm, 1.7 μm) was used for chromatographic separation. The mobile phase was acetonitrile-0.1% formic acid, with a gradient elution, and the total run time was 4 min. Electrospray was used in the positive ion mode, and the multiple reaction monitoring (MRM) mode was for quantification. The acetonitrile precipitation method was used to remove protein-treated mouse plasma and tissue homogenate samples. In the concentration range of 2–5000 ng/g, hirsutine and hirsuteine in tissues showed good linearity (r > 0.995), and the lower limit of quantification was 2 ng/g. In the plasma and liver tissues, the interday and intraday precision of hirsutine and hirsuteine was less than 15%, the accuracy was between 90.9% and 110.1%, and the average recovery was better than 73.0%. The matrix effect was between 86.2% and 104.7%. The results showed that the precision, accuracy, recovery, and matrix effects meet the requirements for the study on the distribution of hirsutine and hirsuteine. After intraperitoneal administration of 10 mg/kg hirsutine and hirsuteine in mice, the distribution levels were highest in liver and kidney tissues, followed by the spleen and lung. Hirsutine and hirsuteine were low in brain tissue, but had obvious distribution, suggesting that they may pass through the blood-brain barrier.